Cardiovascular Risk Factors in Childhood and Adulthood and Cardiovascular Disease in Middle Age - Kartiosuo, Noora; Raitakari, Olli T.; Juonala, Markus; Viikari, Jorma S. A.; Sinaiko, Alan R.; Venn, Alison J.; Jacobs; David R.; Jr; Urbina, Elaine M.; Woo, Jessica G.; Steinberger, Julia; et al. (JAMA Network, 2025)
Importance: Recent evidence suggests that childhood levels of serum lipids, blood pressure, body mass index (BMI), and smoking contribute to adult risk of cardiovascular disease (CVD). Evidence is lacking on whether this is independent of adult risk levels.
Objective: To quantify direct and indirect effects of childhood risk factors on adult CVD via adulthood risk factors using mediation analysis, and to quantify their relative importance during different life-course stages using a life-course approach.
Design, setting, and participants: This prospective cohort study followed participants from the US, Finland, and Australia from childhood (1970s-1990s) until 2019, with data on CVD risk factors in childhood and adulthood. Longitudinal childhood and adulthood risk factors were summarized to describe BMI, lipids, and blood pressure cumulatively. Childhood and adulthood smoking were assessed with questionnaires. Data analysis was performed May 2022 to August 2023.
Main outcomes and measures: The primary outcomes were fatal and nonfatal cardiovascular events in adulthood. Mediation analysis was used to estimate the direct and indirect effects of the childhood risk factors with CVD events, reported as incidence rate ratios (RRs) and 95% CIs.
Results: A total of 10 634 participants (4506 male participants [42.4%]; mean [SD] age at childhood visit, 13.3 [3.0] years; mean [SD] age at adulthood visit, 32.3 [6.0] years) were included in the cohort. The mean (SD) age at CVD event or censoring was 49.2 (7.0) years. The median (IQR) follow-up time was 23.6 (18.7-30.2) years. Childhood risk factors, (low-density lipoprotein cholesterol [LDL-C], total cholesterol [TC], triglycerides, systolic blood pressure [SBP], smoking, BMI, and a combined score of these) were associated with CVD. BMI (direct effect for incidence RR per 1 SD unit, 1.18; 95% CI, 1.05-1.34) and LDL-C (direct effect incidence RR, 1.16; 95% CI, 1.01-1.34) in particular were found to play an important role via direct pathways, whereas the indirect effects were larger for TC, triglycerides, SBP, and the combined score. Childhood smoking only affected CVD via adulthood smoking. Life-course models confirmed that for the risk of CVD, childhood BMI plays nearly as important role as adulthood BMI, whereas for the other risk factors and the combined score, adulthood was the more important period.
Conclusions and relevance: In this cohort study of 10 634 participants, childhood risk factors were found to be associated both directly and indirectly to adult CVD, with the largest direct effect seen for BMI and LDL-C. These findings suggest that intervention for childhood risk factors, in particular BMI, is warranted to reduce incidence of adult CVD as it cannot be fully mitigated by risk factor management in adulthood.